E-READINESS SEBAGAI MODEL EVALUASI E-LEARNING DALAM MENCAPAI E-LEARNING MATURITY - Eko Yulian; Utama Andri Arjita (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
In the implementation of an e-learning system, there are many obstacles faced by an organization because there is no careful planning in making an e-learning system. Therefore, it is necessary to analyze the level of organizational readiness in implementing e-learning (readiness of e-learning). The BPS Education and Training Center's e-Readiness level is in condition 3, which describes the readiness that needs a lot of improvement. By knowing the e-learning readiness index of an organization, it is hoped that it can be the basis for preparing and improving the e-learning system so that a system with a good level of maturity is expected. Results Based on research at the BPS Education and Training Center, there is a gap in the level of development of e-learning development. The strategy is expected to be obtained through activities contained in the eMM framework and has been confirmed directly by experts.